The Archaeopark at Netolice: Reconstruction of an early medieval hillfort in South Bohemia. Circumstances of its establishment, impact, and perspectives - Chvojka, Ondřej; Beneš, Jaromír; Pták, Martin; Chytráček, Miloslav; Růžička, Petr; Gruber, Heinz; Divišová, Michaela; Husty, Ludwig; Michálek, Jan; Bumerl, Jiří; Sandner, Ruth; Hojerová, Hana; et al. (Verlag Marie Leidorf GmbH, 2016)
This study is dedicated to the Archaeopark at Netolice, which was built on the site of the former Přemyslid castle "Na Jánu" in Netolice. The authors of the study summarize the early medieval development of fortification and the archaeological excavations that were carried out in the course of the construction of the archaeopark. One of the main objectives of the article is to familiarize the experts with the difficulties of establishing and subsequent pursuing of the archaeopark.
Archaeopark v Netolicích: rekonstrukce raného středověkého hradiště v jižních Čechách. Okolnosti jeho vzniku, vlivu a perspektiv
Keywords: early medieval hillfort; South Bohemia; archaeology; archaeopark at Netolice; raně středověké hradiště; jižní Čechy; archeologie; Archeopark v Netolicích